La restauración del color en el cine mudo: del Desmetcolor a la restauración digital - Stara, Daniela (Cuadernos de Documentación Multimedia, 2009)
Taking as a fact that the production of silent cinema was in a great deal in color, and analyzing the types of coloring techniques of that time, this article wants to inform about the actual methods (either analogical and digital) of restoration of those old colors.
Keywords: Film restoration; Coloring techniques; Silent films